2022
DOI: 10.1186/s42238-022-00135-y
|View full text |Cite
|
Sign up to set email alerts
|

A description of self-medication with cannabis among adults with legal access to cannabis in Quebec, Canada

Abstract: Objective Cannabis is increasingly used for medical purposes, particularly in countries like Canada where cannabis was recently legalized for recreational use. We aimed to assess self-medication with cannabis post-cannabis legalization among adults in the Canadian province of Quebec. Methods This is a cross-sectional online survey of a self-selected convenience sample conducted in Quebec, Canada, from November 2020 to January 2021. Individuals aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The median daily dose of oral THC for the AECeR cohort is approximately 10% of the average recreational user. Recreational cannabis even for medical purposes is largely inhaled [32]. Inhaled cannabis is rapidly absorbed and reaches peak serum concentration (Cmax) in minutes giving the well-known "high".…”
Section: Plos Onementioning
confidence: 99%
“…The median daily dose of oral THC for the AECeR cohort is approximately 10% of the average recreational user. Recreational cannabis even for medical purposes is largely inhaled [32]. Inhaled cannabis is rapidly absorbed and reaches peak serum concentration (Cmax) in minutes giving the well-known "high".…”
Section: Plos Onementioning
confidence: 99%
“…Psychological distress refers to non-specific symptoms that include stress, anxiety and depression; increased levels of psychological distress may indicate the beginning of serious conditions such as major depressive disorder, anxiety disorder, schizophrenia, somatization disorder, or a variety of other clinical conditions [ 4 ]. In practice, it is often seen that many patients deny any symptoms of psychological distress [ 5 , 6 ] and often they self-treat with ethanol [ 7 ] and/or social recreational agents [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings from the National Cannabis Survey also found that, among the 14% of Canadian respondents 16 years of age and over using cannabis for medical purposes, 78% did so without medical authorisation 40. Yet, some adults who self-medicate with cannabis also report a desire to access health professionals for advice related to their use 41. A qualitative study of family physicians demonstrated they were often hesitant to guide patients on medical cannabis use, including a reluctance to authorise its use, due to concerns about the potential for harm and a feeling they lacked education about its therapeutic benefit 42.…”
Section: Discussionmentioning
confidence: 99%